Improving photosynthesis by scattering hydrogel fiber–enabled volumetric illumination - Yijie Cheng; Mohamed A. Elhabet; Akhiri Zannat; Lenan Zhang; Xuanjie Wang; Yuchen Bian; Siyuan Rao; Yan Liu; Wei Liao; Yoichiro Tsurimaki; Xinyue Liu (Proceedings of the National Academy of Sciences, 2026)
Photosynthetic biomanufacturing offers a sustainable route to generate valuable bioproducts by harnessing microorganisms such as algae to convert sunlight and carbon dioxide into biomass. A major barrier to efficient production is that light penetrates poorly into dense algal cultures, restricting photosynthesis to a thin surface layer and severely limiting the solar energy that can be utilized for algal growth and biomass production. Here, we present a material-based strategy to overcome this fundamental bottleneck by deploying bulk-scattering, index-matched optical fibers that redistribute sunlight uniformly throughout the culture volume. These fibers are made from amorphous hydrogels with a refractive index closely matched to that of algal media and contain scattering nanoparticles that redirect light to achieve volumetric illumination. When integrated into solar-powered algal systems, the fibers enable dense and sustained algal growth at 0.8 to 1.4 g L −1 over 2 mo of semicontinuous outdoor cultivation, resulting in volumetric biomass productivity of 0.15 g L −1 day −1 and photosynthetic efficiency of 1.4%, significantly higher compared to algal systems without fibers. This study demonstrates the transformative potential of optical modulation to the long-standing low productivity in dense algal culture, providing a scalable, sustainable, and efficient pathway for solar-driven biomanufacturing.